Instruments for Measuring Recovery among Serious Mental Illness: A Systematic Review of Systematic Review - Thongsalab, Jutharat; Yunibhand, Jintana; Uthis, Penpaktr (Basic and Applied Nursing Research Journal, 2022)
Background: Indicators of recovery outcomes are selected by mental health nurses beginning with a commitment to a holistic and client-centered view of recovery. The purpose of the review aimed to bring together the results of previous systematic reviews on instruments for assessing the recovery of people with serious mental illnesses. Methods: A systematic literature review was carried out using the guidelines of the Joanna Briggs Institute for systematic reviews. A literature search using The ScienceDirect, SpringerLink electronic databases, Google Scholar, and a Google search engine was used. Searching in literature published between January 2010 and December 2020, supplemented by reference tracking and Internet searches. The authors independently reviewed all titles, assessed articles’ eligibility for inclusion, determined a methodological quality score for each included article and extracted relevant data. Results: Out of 19,724 articles related to the title for potential inclusion in this review, four met the inclusion criteria. The eligibility tools appear to have been studied in various settings and with varied types of patients but are still congruent with SIM. Most importantly, the reviews identified several methodological limitations across the original studies. The lack of a ‘gold standard. This review found twenty-two dimensions in personal recovery instruments and twenty-one in mental health services orientation. Also, many recovery assessment tools are available for the serious mental illness population. However, there is limited evidence about their psychometric properties. Conclusion: Three instruments were found that could measure the personal recovery of people with serious mental illnesses. Those instruments' psychometric properties and cultural adaptation are recommended for further studies.